Sistem Informasi Geografis Web Untuk Menentukan Objek Wisata Kota Bukittinggi - Andriyani, Novi; Sularno, Sularno (Jurnal Sistem Informasi Dan Informatika, 2023)
The city of Bukittinggi is a city with cool air, because it is surrounded by the hills of Singgalang and Merapi, so that the city of Bukittinggi is in great demand by local and foreign tourists. This is because the city of Bukittinggi has interesting tourist attractions. However, for tourists who come to the city of Bukittinggi, several problems arise. And, of course, tourists don't know the area they are visiting. But finding the location of a tourist attraction is certainly a difficult thing to do without knowing the ins and outs of the place to be visited. Meanwhile, according to the latest data collected, there are 10 tourist attractions spread across the city of Bukittinggi. Why less? Considering that the City of Bukittinggi is a small city so that tourists only know the clock time, the Tourism Geographic Information System for the City of Bukittinggi based on a mobile website is expected to be able to overcome this problem. In this system, the user only needs to open a mobile website-based geographic information system online, and the system will display the nearest tourist location that can be reached by the user, so that the user can quickly find the tourist location. Based on the geographic location shown on the map.